2022
DOI: 10.1007/s12011-022-03390-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Lead and Cadmium Combined Heavy Metals on Liver Function and Lipid Metabolism in Mice

Abstract: Although a large number of studies have been conducted on individual lead (Pb) or cadmium (Cd) exposures, the toxicity of combined Pb and Cd exposures is relatively limited. The present study aims to investigate toxicity of Pb-Cd combined heavy metals and its mechanism. A heavy metal exposure model was established by subcutaneous intragastric administration of Pb-Cd (50:1) for 35 days in mice. The body weight, diet, hair color, mental state, liver index, hematological index, biochemical indicators and patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In a study investigating the impact of lead and cadmium on liver function and lipid metabolism in mice, Chen, et al observed that mice exposed to lead and cadmium exhibited lower body weight gain compared to those in the control group. 20 The weight increase in the MC group was slower, showing a decrease of 13.37% compared to the NC group. However, intervention with L. plantarum CCFM8661 significantly improved this situation, as administration of 0.8 × 10 9 CFU L. plantarum CCFM8661 increased the weight gain by 7.11% in mice exposed to mixed heavy metals.…”
Section: Discussionmentioning
confidence: 87%
“…In a study investigating the impact of lead and cadmium on liver function and lipid metabolism in mice, Chen, et al observed that mice exposed to lead and cadmium exhibited lower body weight gain compared to those in the control group. 20 The weight increase in the MC group was slower, showing a decrease of 13.37% compared to the NC group. However, intervention with L. plantarum CCFM8661 significantly improved this situation, as administration of 0.8 × 10 9 CFU L. plantarum CCFM8661 increased the weight gain by 7.11% in mice exposed to mixed heavy metals.…”
Section: Discussionmentioning
confidence: 87%
“…According to previous reports, the results of this study are reasonable and evidence-based. Chronic exposure to Cd resulted in a significant increase in platelet counts and a decrease in lymphocyte counts in mice ( 52 ). Akbar et al showed that Co was not directly cytotoxic to lymphocytes but might affect intracellular molecular homeostasis and thus inhibit lymphocyte proliferation ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that DHA can effectively reduce the activities of serum AST and ALT and restore the integrity of liver tissue. Cd is transported through the blood to various organs, and liver damage caused by Cd leads to increased membrane fluidity, causing enzymes in the liver to leak into the blood [ 36 ]. Therefore, serum AST and ALT are important markers of hepatocyte injury [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%